2018
DOI: 10.1177/0192513x18764542
|View full text |Cite
|
Sign up to set email alerts
|

“It’s My Language, My Culture, and it’s Personal!” Migrant Mothers’ Experience of Language Use and Identity Change in Their Relationship With Their Children: An Interpretative Phenomenological Analysis

Abstract: The question of how migrants’ language use affects their ethnic identity has received considerable attention in the literature. There is, however, little understanding of how this relationship manifests or is negotiated in interethnic families. This article presents an in-depth exploration of Spanish mothers’ experiences of Spanish- and English-language interactions with their English-born children. Semistructured interviews were conducted with Spanish mothers living in Britain in interethnic partnerships and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 51 publications
(69 reference statements)
3
18
0
Order By: Relevance
“…This study has also identified inconsistencies between positive attitudes and actual practices where nearly a half of the parents (47%) do not use Javanese in child-parent communication (See the red bar in Figure 4). This is consistent with findings from immigrant families where transmitting a heritage language also becomes a daily struggle due to social change (Farr et al, 2018). Taking a reflection on these findings, I argue that family should be attributed as a complementary element to ethnolinguistic vitality in the context of continuous use of heritage and ethnic languages.…”
Section: Attitudes On Intergenerational Transmission Of Javanesesupporting
confidence: 86%
See 2 more Smart Citations
“…This study has also identified inconsistencies between positive attitudes and actual practices where nearly a half of the parents (47%) do not use Javanese in child-parent communication (See the red bar in Figure 4). This is consistent with findings from immigrant families where transmitting a heritage language also becomes a daily struggle due to social change (Farr et al, 2018). Taking a reflection on these findings, I argue that family should be attributed as a complementary element to ethnolinguistic vitality in the context of continuous use of heritage and ethnic languages.…”
Section: Attitudes On Intergenerational Transmission Of Javanesesupporting
confidence: 86%
“…Indicated by the red bar in Figure 2, 69% perceived lack of Javanese proficiency would definitely determine their self-belonging. Along similar lines, Farr et al (2018) maintained that heritage language fluency serves as a means of indexing ethnic memberships and facilitates a sense of belonging. To put it differently, group feelings are often more easily articulated when using the group's own language.…”
Section: Attitudes On Javanese Proficiency and Ethnic Identity Markermentioning
confidence: 93%
See 1 more Smart Citation
“…Studying the impact of family communication on the development of immigrant adolescents may help explain the notorious decline in physical, mental, and behavioral health in second-and third-generation immigrants relative to first-generation immigrants, something that has been termed the immigrant paradox [8]. A growing body of research points to communication difficulties between immigrant parents and their adolescent children (e.g., [9][10][11][12][13]), but the impact of these difficulties on adolescent development remains an understudied area of research. A new way of conceptualizing how family risk and resilience might interact to impact adolescent development in immigrant families is a phenomenon we are calling Shared Language Erosion.…”
Section: Introductionmentioning
confidence: 99%
“…It is because the culture formed in human's mind can be understood through language. The linguistic meaning from a language truly can be determined by the context of culture where that language exists (Clayton, 2017;Farr, Blenkiron, Harris, & Smith, 2018;Pennycook, 2017). Therefore, in a language especially in this case, a lexicon has various perspectives or perceptions from the speakers from the culture, ideology, and others.…”
mentioning
confidence: 99%